Vitamin B12 and ketorolac on pain in Long Evans rats - Rahman, Md Mizanur; Begum, Noorzahan; Ali, Taskina; Rouf, Mahadi Abdur; Masood, Shahriar (Journal of Bangladesh Society of Physiologist, 2016)
Background: Effects of vitamin B12 on pain have been demonstrated in different animal and human studies. But comparison of these effects with similar effects of ketorolac tromethamine (KT) and their combination have not been established. Objective: To assess the effects of vitamin B12 on pain and also to compare them with those of the combinations of vitamin B12 with KT in rat models. Methods: This experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2015 to February 2016. For this, 20 (twenty) Long Evans rats (215±35 gm) of both sexes were divided into control (A, with 5 ml/kg normal saline) and experimental (B1, with 15 mg/kg B12; B2, with 10 mg/kg KT; B3, with B12+KT) groups with 5 rats in each group. All the drugs and vitamin were administered intraperitoneally in a single dose just one hour before formalin test. To evaluate the treatments effect on nociceptive pain, early phase (1st- 5th minutes); on central analgesic system, interphase (6th-15th minutes); and on inflammatory pain, late phase (16th-60th minutes) of the formalin test, were observed. In all phases, total frequency of jerking and total duration of flexing and licking of the right hind paw were counted after administration of subcutaneous formalin (50 ?l, 2.5%) injection. Statistical analysis was done by ANOVA, followed by Bonferroni post hoc test. In the interpretation of results, p?0.05 was considered as significant. Results: B12 lowered only the jerking frequency and KT lowered both jerking frequency and flexinglicking duration significantly (p?0.001) in the late phase of formalin test. On the other hand, combination of B12 and KT significantly (p?0.001) lowered both the study variables in all 3 phases of formalin test. Conclusion: From this study it may be concluded that, vitamin B12 possess analgesic effects and combination of B12 with KT is more effective than those of their individual administration. Bangladesh Soc Physiol. 2016, December; 11(2): 63-69